Kemampuan Berpikir Kritis Siswa pada Pembelajaran Online Inquiry dan Problem Based Learning (PBL) - Putri, Febby Ayuni Esya; Syaiful, Syaiful; Siburian, Jodion (Edumatica : Jurnal Pendidikan Matematika, 2021)
This research was motivated by teachers who must continue to help their students to enhancestudent's critical thinking skills even in COVID-19 pandemic situation. Online Inquiry and Problem Based Learning (PBL) with Zoom Cloud Meeting platform was used because based on previous research, Inquiry learning and PBL can improve student's critical thinking skills. The purpose of this study was to see the differences of junior high school student's critical thinking skills after being taught by online Inquiry learning and PBL in terms of student's initial abilities and to see the interaction between Inquiry, PBL, and initial ability with student's critical thinking. This research was used quasi experimental nonequivalent control group design, conducted in 8th grade of Junior High School 7 Jambi City using 3 classes; 2 experimental classes and 1 control class selected by the simple random sampling method. The results of this study were tested with one way and two way ANOVA, showing that there were differences of student's critical thinking abilities with high, medium and low initial abilities after being taught by online Inquiry learning and PBL learning, but there was no interaction between online Inquiry learning and PBL, and student's initial ability with student's critical thinking.